COMPARATIVE EFFECTS OF BUPRENORPHINE AND DEXMEDETOMIDINE AS ADJUVANTS TO BUPIVACAINE SPINAL ANAESTHESIA IN ELDERLY MALE PATIENTS UNDERGOING TRANSURETHRAL RESECTION OF PROSTRATE (TURP) AND TRANSURETHRAL RESECTION OF BLADDER TUMOR (TURBT): A RANDOMIZED PROS - Dr Aman Kujur; Dr Afrin Khoja (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Transurethral resection of the prostate (TURP) or transurethral resection of bladder tumor (TURBT) is a commonly performed urological procedure in elderly men with spinal anaesthesia being the technique of choice. Use of low-dose spinal anesthetic drug with adjuvants is desirable. The present study was undertaken to evaluate and compare the characteristics of subarachnoid blockade, hemodynamic stability, time of first analgesia request and adverse effects of intrathecal buprenorphine and dexmedetomidine as an adjuvant to 0.5% hyperbaric bupivacaine for lower abdominal surgeries. Methods: A total 60 elderly male patients of ASA status I/II, aged 60 years and above, scheduled for elective TURP and TURBT were enrolled and divided into two groups namely Group B and Group D of 30 each. Patients in Group B received 60μg of buprenorphine with 0.5% bupivacaine 14 mg intrathecally whereas patients in Group D received 5μg of dexmedetomidine with 0.5% bupivacaine 14 mg intrathecally. The onset time to peak sensory level, motor block, haemodynamic variables, duration of motor block, analgesia and any adverse effects were noted. Results: There was no significant difference between groups regarding demographic characteristics and type of surgery. The motor, sensory blockade and time of rescue analgesia were significantly prolonged in Group D compared to Group B. There was no significant difference in haemodynamic variables although Group D had lower Heart Rate (HR) than Group B. Conclusion: Dexmedetomidine as an intrathecal adjuvant with 0.5% hyperbaric bupivacaine prolonged anaesthesia, analgesia with better degree of sedation and reduced need of rescue analgesics with fewer side effects when compared to intrathecal buprenorphine